Infrared and Raman spectroscopy in forensic science - Chalmers, John M.; Edwards, Howell G. M., 1943-; Hargreaves, Michael D. (Chichester, West Sussex, UK ; Hoboken : Wiley, 2012)
'This book will provide a survey of the major areas in which information derived from vibrational spectroscopy investigations and studies have contributed to the benefit of forensic science, either in a complementary or a unique way. This is highlighted by examples taken from real case studies and analyses of forensic relevance, which provide a focus for current and future applications and developments'--
Includes bibliographical references and index.
Keywords: Forensic sciences; Infrared spectroscopy; Raman spectroscopy; Criminal investigation